Front Cover: Scalable Creation of Deep Silicon‐Vacancy Color Centers in Diamond by Ion Implantation through a 1‐µm Pinhole (Adv. Quantum Technol. 12/2021). Issue 12 (9th December 2021) - Hunold, Lukas; Lagomarsino, Stefano; Flatae, Assegid M.; Kambalathmana, Haritha; Sledz, Florian; Sciortino, Silvio; Gelli, Nicla; Giuntini, Lorenzo; Agio, Mario
Abstract : Diamond color centers represent a promising resource for quantum photonics applications. Various approaches based on ion implantation have been developed for their controlled creation, but only at shallow depths. In article number 2100079, Lukas Hunold, Mario Agio, and co‐workers show the ability to produce diamond color centers with a lateral precision of 1 µm at depths down to 1 µm and they discuss methods to improve the resolution further. These findings facilitate the post‐fabrication of photonic structures and post‐processing of diamond‐based devices.